Clinical Survey of Decreased Blood Flow Rate in Continuous Renal Replacement Therapy: A Retrospective Observational Study - Makoto Harada; Masafumi Ooki; Kaede Kohashi; Tohru Ichikawa; Mamoru Kobayashi (Critical Care Research and Practice)
Background. Continuous renal replacement therapy (CRRT) is an essential procedure for patients with acute kidney injury in intensive care. It is important to maintain an adequate blood flow rate during CRRT. Several previous studies have reported the relationships between blood flow rate and filter lifespan, or circuit life, in CRRT. Here, we aim at elucidating the incidence and factors associated with a decreased blood flow rate in CRRT. Methods. This is a retrospective observational study. From January 2014 to June 2017, 119 patients who underwent CRRT in the intensive care unit were enrolled. The definition of a decreased blood flow rate included situations in which the medical staff needed to decrease the blood flow volume. We statistically analyzed the association of the decreased blood flow rate with patients’ clinical characteristics. Results. Of 119 patients, 52 required a decreased blood flow rate during CRRT. Almost half of the cases occurred within one day of starting CRRT. None of the clinical factors (age, sex, height, sequential organ failure assessment (SOFA) score, catheter position, systemic infection, albumin, hemoglobin, and activating coagulation time) were significantly associated with decreased blood flow rate. Conclusions. A decreased blood flow rate often occurs during CRRT. Clinical factors significantly associated with the occurrence of the decreased blood flow rate were not detected in the current study. Further investigation regarding the occurrence of a decreased blood flow is warranted.